Social behavior and cooperative breeding in a precocial species: The Kalij Pheasant (Lophura leucomelanos) in Hawaii. (7th September 2016) - Zeng, Lijin; Rotenberry, John T.; Zuk, Marlene; Pratt, Thane K.; Zhang, Zhengwang
Abstract: We examined social behavior and documented cooperative breeding in Kalij Pheasants ( Lophura leucomelanos ) in an introduced population in Hawaii, only the third reported instance of cooperative breeding in Phasianidae. Birds in 31 distinct social groups occupied overlapping home ranges, and group composition remained relatively constant over the 3-yr study period. Each social group contained 1 breeding female and 1 to 6 males. One male was socially dominant in each multiple-male group. Age was the only factor found to determine within-group dominance, suggesting that subordinate males may gain dominance and breeding status by staying in the group. All adults exhibited cooperative behavior, including caring for chicks, agonistic behaviors against conspecific intruders, and vigilance against predators. Average population density was high (3.21 residents per ha), which may lead to habitat saturation in this population. The adult sex ratio was male-biased, with an average M:F ratio of 2.1:1.0. Genetic sex identification of egg samples revealed unbiased primary and secondary sex ratios, which suggests that the bias in adult sex ratio may be caused by differential survival and/or dispersal. Paternity analysis of 13 broods revealed that ~68% of offspring were fathered by the dominant male of the social group, while ~17% were fathered by subordinate males in the group, suggesting that helpers gained some direct benefit by sharing reproduction. We suggest that cooperative breeding may be more common in precocial species than conventionally recognized.